Aboriginal mothers, breastfeeding and smoking - Dawn Gilchrist; Beth Woods; Colin W. Binns; Jane A. Scotth; Michael Gracey (Elsevier, 2004)
Abstract Objective: To document the smoking practices of Aboriginal mothers living in Perth during pregnancy and during the subsequent year while feeding their infants. Method: A cohort of mothers was followed from the time of delivery for 12 months to obtain details of infant feeding practices. A total of 455 mothers delivered between May 2000 and July 2001 and 425 completed the baseline questionnaire. Results: Prior to and during pregnancy, 67% of the mothers smoked regularly. While the rate appeared to decline slightly with the length of breastfeeding, the trend was not significant. The rate of smoking of Aboriginal mothers was significantly greater than for an earlier study of non‐Aboriginal mothers in Perth, where the rate was 28.4%. Among Aboriginal women there was no difference in the percentage of smokers and non‐smokers who initiated breastfeeding. While fewer women who smoked were still breastfeeding at 24 weeks postpartum, compared with non‐smokers (58% vs. 64%), this difference was not significant. Conclusions: The percentage of women smoking in this study is consistent with rates reported in the 2001 National Drug Strategy Household Survey. In other studies, smoking is associated with lower rates of breastfeeding initiation and duration, but this was not the case in the Aboriginal mothers. Implications: Although the high prevalence of smoking identified in this study did not appear to adversely affect breastfeeding, smoking during and after pregnancy does contribute to increased rates of low birth weight and other health problems in early childhood. Targeted antenatal smoking cessation programs are needed for Aboriginal mothers.